Skatt som hållbarhetsfråga - En studie om det personliga ansvaret i förhållande till utvidgade rapporteringskrav för stora bolag - Zingmark,Anna Blanca (2024)
As the world becomes increasingly globalized, new types of challenges arise. Tax planning and tax evasion continue to cause significant harm to the tax bases of countries. To combat this, the OECD has been working on a project called BEPS (Base Erosion and Profit Shifting) since 2013. BEPS consists of 15 actions aimed at countering the erosion of the tax base and profit shifting. The project has been described as the largest global initiative to address various forms of tax avoidance. One of the regulations stemming from BEPS is country-by-country reporting, which was implemented in Sweden in 2017. This regulation requires large multinational corporations to submit country-specific reports detailing their income taxes in each country where they operate. These reports can then be exchanged between tax authorities in all countries that have joined the regulation, to provide as accurate a picture as possible of the actual taxes paid by the corporation. As a further step, the EU has decided to introduce a new regulation in 2023 for corporations operating within the EU, requiring these income tax reports to be publicly disclosed for general scrutiny. This regulation has been criticized for potentially undermining the progress made with country-by-country reporting. If the public income tax reporting is not adhered to, the board of directors and the CEO can be held personally liable. This thesis aims to investigate how personal liability correlates with the increased reporting requirements and the motives behind imposing personal liability on the board and the CEO. This has been done by examining the motives for the public country-by-country directive and comparing the public country-by-country-reporting directive with the country-by-country reporting. The thesis has not definitively identified any reasons for imposing personal liability on the board and the CEO. It has however, become clear that the EU considers public review to be of great importance, necessitating the public disclosure of the reports. The OECD, on the other hand, believes that the confidentiality of country-by-country reporting has been crucial for the smooth implementation of the regulation. The thesis has highlighted a potential challenge in the field of tax law. On the one hand, there is a significant interest in ensuring that companies continue to operate and develop activities that contribute to society, and that they can competitively recruit external individuals to key positions. On the other hand, there is a strong global movement demanding higher transparency and social responsibility. These actors argue that personal liability is essential to ensure that companies comply with regulations. Balancing these two interests presents a complex situation, which does not necessarily imply a real conflict at present. However, it cannot be ruled out that the public disclosure directive will not be the last we see in this area, where personal liability may play an increasingly significant role.
Keywords: skatterätt; EU-rätt